The southernmost record of a Neuryurini Hoffstetter, 1958 (Mammalia, Xenarthra, Glyptodontidae) - González Ruiz, Laureano Raúl (2011)
Fil: González Ruiz, Laureano Raúl. Universidad Nacional de La Patagonia; Argentina